The Modulation of Gamma Oscillations by Methamphetamine in Rat Hippocampal Slices - Li, Yanan; Xie, Xin’e; Xing, Hang; Yuan, Xiang; Wang, Yuan; Jin, Yikai; Wang, Jiangang; Vreugdenhil, Martin; Zhao, Ying; Zhang, Ruiling; Lu, Chengbiao (Frontiers in Cellular Neuroscience, 2019)
Gamma frequency oscillations (γ, 30–100 Hz) have been suggested to underlie various cognitive and motor functions. Methamphetamine (MA), a commonly used recreational drug, enhances brain γ oscillations associated with changes in psychomotor state. Little is known about the cellular mechanism of MA modulation on γ oscillations. We explored the effects of multiple intracellular kinases on MA modulation of γ oscillations in rat hippocampal CA3 area induced by kainate. We found that dopamine receptor 2 (DR2) and N-methyl-D-aspartate receptor (NMDAR) antagonists prevented the enhancing effect of MA on γ oscillation, whereas none of them affected baseline γ oscillation strength. Dopamine receptor 1 (DR1) antagonist and the serine/threonine kinase PKB/Akt inhibitor alone increased γ oscillations but prevented MA enhancement of γ. Protein kinase A, phosphoinositide 3-kinase (PI3K) and extracellular signal-related kinases (ERK) inhibitors had no effect on MA. We propose that the DR1/DR2-Akt-NMDAR pathway play a critical role for the MA enhancement of γ oscillations. Our study provides an insight into the mechanism of acute MA on brain function and a clue for the intervention of MA addiction.